Influence of the procurement surgeon on transplanted abdominal organ outcomes: An SRTR analysis to evaluate regional organ procurement collaboration. Issue 8 (18th March 2019) - Serrano, Oscar K.; Vock, David M.; Snyder, Jon J.; Chinnakotla, Srinath; Kandaswamy, Raja; Pruett, Timothy L.; Matas, Arthur J.; Finger, Erik B.
Abstract : Single‐center studies have demonstrated regional organ procurement collaboration to reduce travel redundancy and improve procurement efficiency. We studied deceased donor kidney, liver, and pancreas transplants performed in the United States between 2002 and 2014 using the Scientific Registry of Transplant Recipients (SRTR). We compared graft failure (GF), death‐censored graft failure (DCGF), and patient death (PD) between organs procured by surgeons from the recipient's center (transplant procurement team [TPT]) versus surgeons from a different center (NTPT). Primary nonfunction (PNF) was assessed for liver and kidney and delayed graft function (DGF) for kidney using mixed‐effects logistic modeling. There were 64 906 liver (61.6% TPT), 118 152 kidney (26.1% TPT), 10 832 simultaneous pancreas kidney (SPK; 56.6% TPT), and 4378 solitary pancreas (SP; 34.0% TPT) transplants. When compared to NTPT, DCGF for organs procured by TPT was significantly less for liver (adjusted HR: 0.93; 95% CI: 0.88‐0.98) and marginally significant for kidney (0.97; 0.93‐1.00) and SPK (0.90; 0.82‐1.00), and not significant for SP (0.98; 0.86 ‐1.11). DGF for TPT kidney was significantly lower (adjusted OR 0.91; 0.87‐0.95). Albeit modest, our findings demonstrate a difference between locally procured organs and those procured by the implanting team. Elucidating the etiology of these differences will enhance regional organ procurement collaboration. Abstract : Organs procured by the implanting transplant team, as compared to those procured by a local surgeon, demonstrate superior outcomes for liver, kidney, and simultaneous pancreas–kidney transplants but not pancreas transplant alone, inciting questions about regional organ procurement collaboration.